2016
DOI: 10.1080/00224499.2016.1221028
|View full text |Cite
|
Sign up to set email alerts
|

Jamaica, Three Years Later: Effects of Intensified Pro-Gay Activism on Severe Prejudice Against Lesbians and Gay Men

Abstract: Jamaica has developed an international reputation for severe anti-gay prejudice. However, in the past few years, between 2012 and 2015, intensified waves of activism have increased the visibility of LGBT Jamaicans and fought for their social and legal inclusion in Jamaican society. This research investigated the effects of that activism by taking advantage of two large, representative surveys of Jamaicans' attitudes toward lesbians and gay men: one in 2012 and one in 2015. Over the 3-year period there were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…To manage this, each measured construct was clearly defined, similarities between the present scales and scales that are more widely used were outlined, and evidence was provided to indicated that the scales were reasonably internally reliable. Also, wherever possible, the items used were similar to (or the same as) those used in prior research in the same context (e.g., West, 2017;West & Cowell, 2015). Contact and anti-gay prejudice in Jamaica 10 = Every year, 3 = 2 to 3 times a year, 4 = Every month, 5 = Every Week) and their monthly income in Jamaican dollars 1 (1 = Under $20,000, 2 = $20, 001 to $35,000, 3 = $35,001 to $75,000, 4 = $75,001 to $125,000, 5 = $125,001 to $175,000, 6 = $175,001 to $225,000, 7 = $225,001 to $275,000, 8 = $275,001 to $325,000, 9 = $325,001 to $375,000, 10 = $375,001 to $425,001, 11 = $425,001 to $475,000, 12 = $475,000 and above).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To manage this, each measured construct was clearly defined, similarities between the present scales and scales that are more widely used were outlined, and evidence was provided to indicated that the scales were reasonably internally reliable. Also, wherever possible, the items used were similar to (or the same as) those used in prior research in the same context (e.g., West, 2017;West & Cowell, 2015). Contact and anti-gay prejudice in Jamaica 10 = Every year, 3 = 2 to 3 times a year, 4 = Every month, 5 = Every Week) and their monthly income in Jamaican dollars 1 (1 = Under $20,000, 2 = $20, 001 to $35,000, 3 = $35,001 to $75,000, 4 = $75,001 to $125,000, 5 = $125,001 to $175,000, 6 = $175,001 to $225,000, 7 = $225,001 to $275,000, 8 = $275,001 to $325,000, 9 = $325,001 to $375,000, 10 = $375,001 to $425,001, 11 = $425,001 to $475,000, 12 = $475,000 and above).…”
Section: Methodsmentioning
confidence: 99%
“…One potentially important solution, however, has thus far been absent from these representative and comparative investigations of prejudice reducing strategies in Jamaicaintergroup contact. Some research has identified contact, and related contact-based interventions, as potential solutions (West & Hewstone, 2012a;, and positive contact has been suggested as a crucial addition to other strategies currently in use, such as collective action (West, 2017). However, it is important to investigate the relative potential utility of contact by comparing it to other variables that predict levels of sexual prejudice in Jamaica.…”
Section: Predictors Of Prejudice Against Lesbians and Gay Men In Jamaicamentioning
confidence: 99%
See 3 more Smart Citations